A "weak acid and weak base" type fluorescent probe for sensing pH: mechanism and application in living cells. Issue 36 (4th July 2019) - Jiao, Chunpeng; Pang, Jingxiang; Shen, Li; Lu, Wenjuan; Zhang, Pingping; Liu, Yuanyuan; Li, Jing; Jia, Xianhui; Wang, Yanfeng
Abstract : When the probe was in the protonation process, the fluorescence intensity gradually decreased, whereas when the probe was in the deprotonation process, the fluorescence intensity gradually increased. Abstract : A simple pH fluorescent probe, N -(6-morpholino-1, 3-dioxo-1 H -benzo[ de ]isoquinolin-2(3 H )-yl) isonicotinamide (NDI ), based on naphthalimide as the fluorophore and isonicotinic acid hydrazide as the reaction site was synthesized and characterized. It is useful for monitoring acidic and alkaline pH. The results of pH titration indicated thatNDI exhibits obvious emission enhancement with a p K a of 4.50 and linear response to small pH fluctuations within the acidic range of 3.00–6.50. Interestingly, NDI also displayed strong pH-dependent characteristics with p K a 9.34 and linearly responded to an alkaline range of 8.30–10.50. The sensing response mechanism was confirmed by 1 H NMR and ESI-MS spectroscopy. The mechanism of the optical responses ofNDI toward pH was also determined by density functional theory (DFT) calculations. In addition, NDI displayed a highly selective and sensitive response to hydrogen ions and hydroxyl ions. The probe was successfully applied to image acidic and alkaline pH value fluctuations in HeLa cells and has lysosomal targeting ability.